Effectiveness of general preconception care accompanied by a recruitment approach: protocol of a community-based cohort study (the Healthy Pregnancy 4 All study) - van Voorst, Sabine F (BMJ Open, 2015)
INTRODUCTION: Promotion of healthy pregnancies has gained high priority in the Netherlands because of the relative unfavourable perinatal outcomes. In response, a nationwide study Healthy Pregnancy 4 All (HP4ALL) has been initiated. One of the substudies within HP4ALL focuses on preconception care (PCC). PCC is an opportunity to detect and eliminate risk factors before conception to optimise health before organogenesis and placentation. The main objectives of the PCC substudy are (1) to assess the effectiveness of a recruitment strategy for the PCC health services and (2) to assess the effectiveness of individual PCC consultations. METHODS/ANALYSIS: Prospective cohort study in neighbourhoods of 14 municipalities with perinatal mortality and morbidity rates exceeding the nation's average. The theoretical framework of the PCC substudy is based on Andersen's model of healthcare utilisation (a model that evaluates the utilisation of healthcare services from a sociological perspective). Women aged 18 up to and including 41 years are targeted for utilisation of the PCC health service by a four armed recruitment strategy. The PCC health service consists of an individual PCC consultation consisting of (1) initial risk assessment and risk management and (2) a follow-up consultation to assess adherence to the management plan. The primary outcomes regarding the effectiveness of consultations is behavioural change regarding folic acid supplementation, smoking cessation, cessation of alcohol consumption and illicit substance use. The primary outcome regarding the effectiveness of the recruitment strategy is the number of women successfully recruited and the outreach in terms of which population is reached in comparison to the approached population. Data collection consists of registration in the database of women that enrol for a visit to the individual PCC consultations (women successfully recruited), and preconsultation and postconsultation measurements among the included study population (by questionnaires, anthropometric measurements and biomarkers). Sample size calculation resulted in a sample size of n=839 women. ETHICS AND DISSEMINATION: Approval for this study has been obtained from the Medical Ethical Committee of the Erasmus Medical Center of Rotterdam (MEC 2012-425). Results will be published and presented at international conferences.